Pengaruh Latihan Memukul Bola Digantung Terhadap Ketepatan Smash Bola Voli - Suwarda Gadis Notriya; Sudirman Husin; Ade Jubaedi (JUPE (Jurnal Penjaskesrek), 2018)
This study aims to determine the effect of hitting the ball is hung on improving the accuracy of smash participants extracurricular volleyball high school girls Paramarta 1 Seputih Many Central Lampung. This research uses pseudo experimental method, this research design is